Effect of Ashitaba Leaf as Antibiofilm Against Pseudomonas aeruginosa and Staphylococcus aureus - Luluk Aniqoh Meliana Putri; Ismi Rahmawati; Opstaria Saptarini (STRADA : Jurnal Ilmiah Kesehatan, 2025)
Infection is one of the serious health problems that will continue to grow in Indonesia. Indonesian people have used herbal medicines derived from plants such as ashitaba leaves which contain chemical compounds tannin, alkaloids, flavonoids and saponins to treat several diseases. This study aims to see the potential of extracts and fractions (n-hexane, water and ethyl acetate) to inhibit the formation, destroy biofilms against Pseudomonas aeruginosa and Staphylococcus aureus. The method used is antibacterial testing using the dilution method, observation of bacterial cell morphology using SEM. Results active ashitaba leaf fraction inhibits the formation and degrades Pseudomonas aeruginosa and Staphylococcus aureus biofilms is water. The location of the most active water fraction against Staphylococcus aureus bacteria is on the bacterial cell wall. The water fraction has antibacterial activity against Staphylococcus aureus with an MBC value of 12.5%, the location of the water fraction is on the bacterial cell wall.